2016
DOI: 10.4172/2315-7844.1000198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Justice on Organizational Citizenship Behavior: A Study of Health Sector of Pakistan

Abstract: Work related behaviors and attitudes are affected by organizational citizenship behavior and organizational justice. These two play a vital role in the effective working of an organization. No effective study is conducted on the relationship of organization justice and organizational citizenship behavior in the developing and under developed countries. This study encompasses the connection between organizational justice and organizational citizenship behavior in public hospitals among young doctors. Causal rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
(26 reference statements)
2
17
1
Order By: Relevance
“…To find out what factors were dominant in influencing the formation of OCB at this school, the author distributed questionnaires covering the scope of organizational culture, work climate, perceptions of organizational support, job satisfaction, organizational justice, organizational commitment, and work motivation. The results of pre-research for these factors can be seen in figure (1), which shows that the three research variables, namely organizational culture, organizational justice, and organizational commitment, have a high average no answer, respectively 17.33%, 17.33%, and 20.67%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To find out what factors were dominant in influencing the formation of OCB at this school, the author distributed questionnaires covering the scope of organizational culture, work climate, perceptions of organizational support, job satisfaction, organizational justice, organizational commitment, and work motivation. The results of pre-research for these factors can be seen in figure (1), which shows that the three research variables, namely organizational culture, organizational justice, and organizational commitment, have a high average no answer, respectively 17.33%, 17.33%, and 20.67%.…”
Section: Introductionmentioning
confidence: 99%
“…This pre-research was conducted by distributing questionnaires to 30 employees who had a service period of more than three years. The pre-research results can be seen in table (1). To find out what factors were dominant in influencing the formation of OCB at this school, the author distributed questionnaires covering the scope of organizational culture, work climate, perceptions of organizational support, job satisfaction, organizational justice, organizational commitment, and work motivation.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to Indian automobile sector, interactional justice becomes a significant factor in the augmentation of OCBs as Indians have historically been a collectivist group living in close proximity to each other, thus, highlighting the essential role of fair interpersonal treatment to the employees (Hui et al, 2013). Also, existent research showed that organisational citizenship behaviour is affected directly and indirectly by the organisational justice factors like procedural justice, distributive justice, and interactional justice (Ali, 2016). Mahmoudi et al (2017) acknowledged the mediating role of organisational commitment and trust in the relationship between justice and citizenship behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Rauf (2014) argued that interactional justice plays a prominent role in enhancing citizenship behaviours among school teachers. Ali et al (2017) found that interactional justice among OJ dimensions had a significant influence on overall OCB. Similarly, Elamin and Tlaiss (2015) studied the same topic in a wide range of organizations and industries to determine if interactional justice has a major effect on the different sub-dimensions of OCB: civic virtue, conscientiousness, altruism, courtesy and sportsmanship.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…In addition, Lim and Loosemore (2017) reported that procedural justice increased conscientiousness, courtesy and sportsmanship. Some recent studies have found that interactional justice is a significant predictor of citizenship behaviour (Ali et al, 2017; Al Afari & Abu Elanain, 2014), especially conscientiousness (Tahseen & Akhtar, 2016), civic virtue (Yardan et al, 2014), altruism and courtesy (Ali, 2016) and sportsmanship (Elamin and Tlaiss, 2015). On the other hand, researchers suggested that distributive justice significantly generated OCB (Hart et al, 2016; Ince and Gul, 2011; Kwak, 2016).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%